2009
DOI: 10.1073/pnas.0903264106
|View full text |Cite
|
Sign up to set email alerts
|

Development and diversification of retinal amacrine interneurons at single cell resolution

Abstract: The vertebrate retina uses diverse neuronal cell types arrayed into complex neural circuits to extract, process, and relay information from the visual scene to the higher order processing centers of the brain. Amacrine cells, a class of interneurons, are thought to mediate much of the processing of the visual signal that occurs within the retina. Although amacrine cells display extensive morphological diversity, the molecular nature of this diversity is largely unknown. Furthermore, it is not known how this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
147
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 24 publications
6
147
0
1
Order By: Relevance
“…For example, recent studies have shown that amacrine subtypes arise at distinct times, as predicted by the competence model (38,43), and that further distinctions among them may result from postmitotic fate choices (44). Similarly, analysis of clones containing late-born retinal cell types (rods, amacrines, bipolars, and Müller glia) indicates that stochastic mechanisms acting on a homogeneous population of progenitors can account for the much of the diversity observed (1,45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown that amacrine subtypes arise at distinct times, as predicted by the competence model (38,43), and that further distinctions among them may result from postmitotic fate choices (44). Similarly, analysis of clones containing late-born retinal cell types (rods, amacrines, bipolars, and Müller glia) indicates that stochastic mechanisms acting on a homogeneous population of progenitors can account for the much of the diversity observed (1,45).…”
Section: Discussionmentioning
confidence: 99%
“…The single cell expression profiles have revealed considerable heterogeneity in gene expression in amacrine cells 4 , where it was expected, and in Müller glia cells, where it was unexpected 5 . While an examination of the single amacrine cell data revealed more than 450 genes that were expressed in amacrine cells and excluded from other retinal cell types, none of these genes were expressed in all the amacrine cells 4 .…”
Section: Discussionmentioning
confidence: 99%
“…While an examination of the single amacrine cell data revealed more than 450 genes that were expressed in amacrine cells and excluded from other retinal cell types, none of these genes were expressed in all the amacrine cells 4 . These results most likely arise from the fact that the amacrine cell class is extremely diverse and the underlying heterogeneity is a reflection of the distinct functions of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and Dataset S1). These cells were analyzed previously (18,(28)(29)(30)(31) and classified as RPCs, amacrine cells (ACs), bipolar cells (BPs), photoreceptors (PRs), and Müller glia (MG). Olig2 was present at a signal level of >1,000 in a small subset of 45 RPCs, but in none of the postmitotic retinal ganglion cells (RGCs), ACs, PRs, BPs and MG.…”
Section: Olig2 Expression In Developing Retina During Embryonic and Pmentioning
confidence: 99%